2010
DOI: 10.1673/031.010.19601
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Flour Affects the Efficacy of Aerosolized Insecticides used to Treat the Red Flour Beetle,Tribolium castaneum

Abstract: Experiments were conducted in tightly sealed pilot scale warehouses to assess the efficacy of common aerosolized insecticides on all life stages of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) when exposed in dishes containing 0 to 2 g of wheat flour either under pallets or out in the open. Petri dishes containing 0, 0.1, 1, or 2 g of flour were prepared with 25 eggs, 3rd instars, pupae, or adults and then immediately treated with aerosolized solvent, Pyrethrins, or esfenvalerate. Twenty-four h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 15 publications
(18 reference statements)
3
29
0
Order By: Relevance
“…The recovery and survival were positively correlated with post-exposure time and the amount of flour present in dishes (Arthur and Campbell 2008). Similar observations of knockdown and recovery of T. castaneum life stages exposed to synergized pyrethrins and esfenvalerate applied separately at label rates in pilot scale warehouses were made in the presence of flour as food, both in open and concealed locations (under wooden pallets) (Toews et al 2010). Arthur and Campbell (2008) noticed that T. confusum adults exposed to the synergized pyrithrins in Petri dishes with flour during application and later transferred to new Petri dishes along with the same flour showed increased survival.…”
Section: Distribution and Efficacy Of Aerosol Insecticides In Field Ssupporting
confidence: 65%
See 2 more Smart Citations
“…The recovery and survival were positively correlated with post-exposure time and the amount of flour present in dishes (Arthur and Campbell 2008). Similar observations of knockdown and recovery of T. castaneum life stages exposed to synergized pyrethrins and esfenvalerate applied separately at label rates in pilot scale warehouses were made in the presence of flour as food, both in open and concealed locations (under wooden pallets) (Toews et al 2010). Arthur and Campbell (2008) noticed that T. confusum adults exposed to the synergized pyrithrins in Petri dishes with flour during application and later transferred to new Petri dishes along with the same flour showed increased survival.…”
Section: Distribution and Efficacy Of Aerosol Insecticides In Field Ssupporting
confidence: 65%
“…This discrepancy was partly explained by the fact that the nozzles delivering aerosol particles were directed to the front of the experimental room (Arthur and Campbell 2008), suggesting non-uniform distribution throughout the empty warehouse. Toews et al (2010) observed that exposure to synergized pyrethrin and esfenvalerate applied separately as aerosols at label rates resulted in higher mortality of all life stages of T. castaneum in open locations than in concealed locations (under wooden pallets).…”
Section: Distribution and Efficacy Of Aerosol Insecticides In Field Smentioning
confidence: 94%
See 1 more Smart Citation
“…This improved coverage increases the chance of a stored-product insect encountering the insecticide either during application or afterwards through contact with a treated surface. However, because at a given point in time most of the pest population is located in hidden areas (e.g., inside equipment, accumulated food in cracks and crevices, under pallets, inside packaged food), only a small percentage of individuals are likely to be directly exposed during an aerosol application (Toews et al 2010. The structural complexity of many food facility interiors may also inßuence the dispersal and deposition of aerosol droplets, creating spatial variation in dosage.…”
mentioning
confidence: 99%
“…The majority of the research on efÞcacy has been under laboratory conditions simulating aerosol applications made directly to the insects Arthur 1988Arthur , 1993Arthur and Gillenwater 1990;Tucker et al 2014) or aerosol applications conducted in small rooms (Jenson et al 2010a, Toews et al 2010. Data on the efÞcacy of aerosol insecticides applied at the scale and under the conditions typically found in commercial applications are much more limited.…”
mentioning
confidence: 99%